2020
DOI: 10.1177/1465312520929032
|View full text |Cite
|
Sign up to set email alerts
|

Psychological support for orthognathic patients: Who is doing what?

Abstract: Objective: To investigate: (1) orthodontists’ training experience in the psychological assessment of orthognathic patients and their wish for training/further training; (2) the availability of psychological support, referral patterns and outcomes after referral; (3) and adverse incidents prompting orthodontists to refer patients for psychological assessment. Design: Prospective cross-sectional study. Methods: A 25-item questionnaire was designed to investigate the above mentioned aims. After a pilot study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Interestingly, some stated, that they „test their patients“, whether they want a lot of information or only the least necessary prior to treatment start, but it remained unclear how they did so. Over time, professionals might develop strategies during everyday orthognathic routine to find out what kind of patient they are dealing with – scared or tough; with high, maybe unrealistic expectations or potentially easy to please – but it is crucial to question those strategies once in a while, alter them, if needed, and ask for psychological assistance when trying to properly assess patient’s psychological traits [ 21 , 24 , 25 ]. As we are usually specialized dentists , we might lack detailed communicative knowledge, which is especially important when dealing with orthognathic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some stated, that they „test their patients“, whether they want a lot of information or only the least necessary prior to treatment start, but it remained unclear how they did so. Over time, professionals might develop strategies during everyday orthognathic routine to find out what kind of patient they are dealing with – scared or tough; with high, maybe unrealistic expectations or potentially easy to please – but it is crucial to question those strategies once in a while, alter them, if needed, and ask for psychological assistance when trying to properly assess patient’s psychological traits [ 21 , 24 , 25 ]. As we are usually specialized dentists , we might lack detailed communicative knowledge, which is especially important when dealing with orthognathic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the orthodontist needs to be well equipped with psychological skills that can evaluate and support the OS patient during pre-treatment assessment, pre-surgical preparation, peri-surgical phase, and postoperatively during the healing and finishing phase. A study done in the United Kingdom investigated the orthodontists' training experience in the psychological assessment of OS patients and concluded that although many orthodontists had some sort of training, further training was demanded [4].…”
Section: Psychological Considerationsmentioning
confidence: 99%
“…Do not try to handle them on your own. Adverse incidents such as suicide or suicide attempts after OS have been reported in the literature [4].…”
Section: Assessment Of Risk Factors Predicting Dissatisfaction Of Tre...mentioning
confidence: 99%